Strategic forecasting on the FOMC - Peter Tillmann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
The Federal Open Market Committee (FOMC) of the Federal Reserve consists of voting- and non-voting members. Apart from deciding about interest rate policy, members individually formulate regular inflation forecasts. This paper uncovers systematic differences in individual inflation forecasts submitted by voting and non-voting members. Based on a data set with individual forecasts recently made available it is shown that non-voters systematically overpredict inflation relative to the consensus forecast if they favor tighter policy and underpredict inflation if the favor looser policy. These findings are consistent with non-voting member following strategic motives in forecasting, i.e. non-voting members use their forecast to influence policy deliberation.
Keywords: E43; E52; 330; inflation forecast; forecast errors; monetary policy; monetary committee; Federal Reserve; Geldpolitik; Gruppenentscheidung; Inflation; Prognose; Manipulation; USA